Isolation and structure elucidation of halogenated metabolites from Portieria hornemannii and Portieria tripinnata - Adam, Mohammed (Rhodes University, Faculty of Pharmacy, Pharmacy, 2015)
The red marine algal genus, Portieria, is known to produce a number of potent cytotoxic compounds with anticancer potential. The most important anticancer lead produced by this genus is the compound halomon. Unfortunately, the lack of sufficient quantities of this compound hampered its further development. Two Portieria species, Portieria hornemannii and Portieria tripinnata, are found along the South African coastline. Recent studies, based on DNA analysis, suggest that Portieria hornemannii may in fact be divided into several cryptic species. The current project is part of a larger study designed to investigate the use of secondary metabolites to identify new marine algal species. In this study 1H NMR profiles of the organic extracts of selected Portieria spp were compared in order to identify new species. Selected compounds were then isolated and characterised as potential chemotaxonomic markers. Four halogenated monoterpenes were isolated from Portieria hornemannii. Two of these were new compounds 4-(3-bromo-4-chloro-4-methylpentyl)-3-chlorofuran-2(5H)-one, which were isomers of each other. The two known compounds had been previously isolated from Portieria hornemannii samples off the Madagascar coast. These compounds could prove to be useful as chemotaxonomic marker compounds, as they have never been isolated from any other species of marine algae. Three known halogenated monoterpenes were isolated from Portieria tripinnata. These compounds had been previously isolated from different species of marine algae and therefore, could not serve as chemotaxonomic marker compounds for this species of marine alga. Further work needs to be done on Portieria tripinnata, with regards to its chemistry, as it is a species of marine algae that has not been previously researched.
Keywords: Uncatalogued